EDUKASI SEBAGAI UPAYA PENINGKATAN PENGETAHUAN FIRST AID PADA LUKA BAKAR BAGI IBU: Edukasi sebagai Upaya Peningkatan Pengetahuan First Aid Pada Luka Bakar Bagi Ibu - Setyaningrum, Niken; Sari, Dian Nur Adkhana (Jurnal Pengabdian Masyarakat Kesehatan Terkini, 2024)
Burns are a serious problem throughout the world. It is estimated that every year there are 180,000 deaths due to burns. Emergency conditions in burns include fluid and electrolyte disturbances, pain in the burn area, shortness of breath if inhaling hot air, physical problems if there is density, infection, impaired self-esteem due to scars and even death. One effort to increase knowledge is through health education. This community service activity aims to increase knowledge and understanding of first aid treatment for burn emergencies. Activity methods include pretest, lecture with audiovisual media, leaflets and posttest. The knowledge results show an increase in scores based on the participants' posttest results. Based on these activities, it can be concluded that health education using audiovisual media and leaflets can be used to increase mothers' knowledge and understanding of first aid treatment for burns. It is hoped that participants will be able to apply and always share information with family members.